Physiological explicit of delayed psychological stress response induced by extra neural regulation. (November 2020) - Li, Ming; Chen, Shixiong; Gao, Zhen; Wu, Wanqing; Xu, Lingzheng
Highlights: Acute psychological stress is conducted along a different neural pathway from acute physical stress and causes a conduction delay. The regulation of HRV features produced by acute psychological stress has a delayed and enhanced response compare with acute physical stress. Due to the delayed psychological stress response induced by extra neural regulation, a significant change of HRV features was found at the third minute of psychological stress stage. SDNN, LFpower, HFpower and LF/HF have a linear variation trend during the remaining three to five minutes acute psychologicalstress stage. Abstract: Background and Objective: Acute psychological stress is conducted along a different neural pathway from acute physical stress and causes a conduction delay. This conduction delay reflected on the central nervous system (CNS) as an evaluation process, which allows the human body to make the best response to a stressor based on preceding experiences. However, how this conduction delay reflected on physiological explicit, remains to be studied. Methods: In this work, the variation of nine traditional heart rate variability (HRV) features are studied from twenty-six healthy subjects during acute physical (Cold pressor test (CPT)) and psychological (Stroop color word test (SCWT)) stress on separate occasions. Besides, we discussed ultra-short and short-term HRV analysis and their relationship with acute stress. Results: The experimental results suggest that there was a delayed response of HRV features under acute psychological stress compared with acute physical stress. In addition, during the later stage of stress, four features could differentiate between baseline and acute psychological stress ( p  < 0.05): SDNN, LFpower, HFpower, LF/HF, but these features do not have significant difference during acute physical stress ( p  > 0.05). Conclusions: Due to the delayed psychological stress response induced by extra neural regulation, a significant change of HRV features was found at the third minute of psychological stress stage. And the variation of these features have linear correlation with time during the remaining three to five minutes stress stage ( r  = −0.987, 0.996, −0.952, 0.938 for SDNN, LFpower, HFpower, LF/HF).